Design of Information Technology Governance for Employee Training Data Management using the COBIT 2019 Design Toolkit - Mayer Jeloe Susilo Perdana; Charitas Fibriani (SCOPUS ID=57192643331) (SISTEMASI, 2026)
The rapid advancement of technology in the digital era requires companies to continuously innovate to remain competitive. The implementation of information technology has become a crucial factor in sustaining business operations, particularly in data management and data quality. PT XYZ faces challenges in managing employee training data due to the absence of an integrated system, resulting in data inaccuracies and inconsistencies. The COBIT 2019 framework enables the company to identify gaps between its current governance practices and the governance processes required to support organizational objectives. The recommendations derived from the audit based on the COBIT 2019 Design Factors indicate that the company needs to develop an integrated system as a fundamental foundation for improving data quality and harmonization in alignment with business objectives and decision-making requirements.